2007
DOI: 10.1007/s10815-006-9100-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural cycle cryo-thaw transfer may improve pregnancy outcome

Abstract: Objective: To compare natural vs. hormone replacement treatment (HRT) for cryo-thaw embryo transfer cycles in patients with frozen embryos from previous ART. Design and Settings: Retrospective chart review of 164 patients (242 cycles) who underwent natural or HRT cryo-thaw embryo transfer between January 2002 and April 2005. Main Outcome Measures: Pregnancy rates per transfer in natural and HRT cryo-thaw cycles. Results: The pregnancy rate per transfer was higher with natural cycles (36.76% vs. 22.99%, P = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 14 publications
3
60
1
3
Order By: Relevance
“…In agreement with our findings, some previous studies observed superior outcomes in terms of implantation, clinical pregnancy, and lower miscarriage rates when natural cycles were used [Morozov et al 2007;Orvieto et al 2016;Xiao et al 2012]. Moreover, since FET during a natural cycle is less expensive and more patient-friendly, Peeraer et al [2015] recommended NC regimen as the treatment of choice for women with regular cycles undergoing FET.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with our findings, some previous studies observed superior outcomes in terms of implantation, clinical pregnancy, and lower miscarriage rates when natural cycles were used [Morozov et al 2007;Orvieto et al 2016;Xiao et al 2012]. Moreover, since FET during a natural cycle is less expensive and more patient-friendly, Peeraer et al [2015] recommended NC regimen as the treatment of choice for women with regular cycles undergoing FET.…”
Section: Discussionsupporting
confidence: 91%
“…For example, natural cycles with or without human chorionic gonadotropin (HCG) induced ovulation requires minimum medication and typically carried the least risk for adverse effects and is the least costly. Several groups have reported superior results for this regimen [Morozov et al 2007;Xiao et al 2012]. For the reason of convenience, artificial cycles are often applied to patients with regular menstrual intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Luteal phase support was given in five studies [36,[40][41][42][43]; the ORs for clinical pregnancy and live birth rates were not significantly different (OR 1.32 (95 % CI 0.90-1.93; four studies) and 1.47 (95 % CI 0.72-3.03; two studies), respectively).…”
Section: Tnc Versus Ac Without Suppressionmentioning
confidence: 92%
“…A total of eight studies, all being retrospective cohort studies [35,36,[38][39][40][41][42][43], making a total of 8762 ET cycles, were included.…”
Section: Tnc Versus Ac Without Suppressionmentioning
confidence: 99%
“…[43] установили, что толщина эндометрия при переносе в естественном цикле (ЕЦ) выше (9,95 мм против 8,89 мм; p<0,001), а средний уровень эстради-ола ниже (103,8 пг/мл против 526,1 пг/мл; p<0,001) по сравнению с ЗГТ. Частота наступления беремен-ности также оказалась выше после переноса размо-роженных эмбрионов в ЕЦ (36,76% против 22,99%; p=0,0298).…”
Section: перенос размороженных эмбрионов на фоне згтunclassified